Valerenic acid ameliorates amphetamine-related neurotoxicity by improving hypothalamus tyrosine hydroxylase and histamine-N-methyl transferase enzymes - Khaled M.M. Koriem; Ammar H.A. Naiem (Toxicology Reports)
Background: Narcolepsy, obesity, and attention deficit hyperactivity disorder are all treated with amphetamine (a central nervous system stimulant) while valerenic acid (VA) has a pharmacological effect in the central nervous system. Objectives: The purpose of this study was to ascertain whether VA is able to make amends for neurotoxicity by modifying hypothalamus expressions of the enzymes tyrosine hydroxylase and histamine-N-methyl transferase in rats orally administered with methamphetamine (METH). Methods: There were thirty-six male albino rats split up into six equal groups, Control, VA (5 mg/kg)-treated, and VA (10 mg/kg)-treated groups: For four weeks, normal rats received oral administration of 1 ml of distilled water, 5 mg/kg of VA, and 10 ml/kg of VA once daily. METH-treated, VA (5 mg/kg) prior to METH-treated, and VA (10 mg/kg) before METH-treated groups: normal rats were oral administrated with METH (2.5 mg/kg), 3 days/week for 3 weeks, where the last two groups were oral administrated daily during four weeks at 5 mg/kg and 10 mg/kg VA, starting one week prior to METH administration. Results: METH decreased superoxide dismutase, glutathione peroxidase, catalase, NADPH oxidase, interleukin-10, sucrose preference test, distance traveled test, and center square entries test, ATPase activity and the enzymes tyrosine hydroxylase and histamine-N-methyl transferase but increased malondialdehyde, conjugated dienes, oxidative index, serotonin, dopamine, norepinephrine, γ-aminobutyric acid, tumor necrosis factor-α, interleukin-1β, interleukin-6, nuclear factor kappa B levels, the center square duration test, tail suspension test, and forced swimming test. in the METH-treated animals' brain in contrast to the control group. After four weeks of oral administration of VA to METH-treated rats, all of these parameters returned to levels that were nearly control, indicating that a higher dose was more effective than a lower one. Conclusion: VA ameliorated METH-related neurotoxicity by improving hypothamalus expressions of the enzymes tyrosine hydroxylase and histamine-N-methyl transferase.